Net benefit of statins for primary prevention of cardiovascular disease in people 75 years or older: a benefit-harm balance modeling study - Henock G. Yebyo; Hélène E. Aschmann; Dominik Menges; Cynthia M. Boyd; Milo A. Puhan (SAGE Publishing, 2019)
Background: We determined the risk thresholds above which statin use would be more likely to provide a net benefit for people over the age of 75 years without history of cardiovascular disease (CVD). Methods: An exponential model was used to estimate the differences in expected benefit and harms in people treated with statins over a 10-year horizon versus not treated. The analysis was repeated 100,000 times to consider the statistical uncertainty and produce a distribution of the benefit-harm balance index from which we determined the 10-year CVD risk threshold where benefits outweighed the harms. We considered treatment estimates from trials and observational studies, baseline risks, patient preferences, and competing risks of non-CVD death, and statistical uncertainty. Results: Based on average preferences, statins were more likely to provide a net benefit at a 10-year CVD risk of 24% and 25% for men aged 75-79 years and 80-84 years, respectively, and 21% for women in both age groups. However, these thresholds varied significantly depending on differences in individual patient preferences for the statin-related outcomes, with interquartile ranges of 21-33% and 23-36% for men aged 75-79 years and 80-84 years, respectively, as well as 20-32% and 21-32% for women aged 75-79 years and 80-84 years, respectively. Conclusions: Statins would more likely provide a net benefit for primary prevention in older people taking the average preferences if their CVD risk is well above 20%. However, the thresholds could be much higher or lower depending on preferences of individual patients, which suggests more emphasis should be placed on individual-based decision-making, instead of recommending statins for everyone based on a single or a small number of thresholds.